Clamping root-cutting end-effector for harvesting fresh safflower - Zhang, Zhenguo; Zeng, Chao; Xu, Peng; Shi, Ruimeng; Wang, Yunze; Xing, Zhenyu (International Journal of Agricultural and Biological Engineering, 2025)
A suitable picking method for the end-effector is the key to achieving low-damage picking. Due to the high moisture content of fresh safflower and its fragile filaments, achieving low-damage picking is a challenge for most picking robots. In this paper, a clamping and root-cutting end-effector for harvesting fresh safflower is developed. It utilizes dual rollers to pre-clamp the filaments and a blade to root-cut the safflower necking to realize the safflower harvesting operation. A mechanical model of dual rollers-blade-filaments cutting was constructed to theoretically analyze the harvesting process. The key factors affecting the performance of the end-effector were identified as blade feed speed, rotation speed, and roller clearance. Using the filament removal rate and damage rate as evaluation indices, the central composite design was carried out. The mathematical model between the test factors and evaluation indices was obtained, and the regression model was optimized with multiple objectives. Finally, the optimal combination of parameters was determined to be a blade feed speed of 40 mm/s, a rotation speed of 318 r/min, and a roller clearance of 0.60 mm. The field test was conducted under the optimal parameter combination, and the filament removal rate and damage rate were 91.25% and 5.57%, respectively. The optimized results had an error of less than 5%, indicating that the designed end-effector can harvest filaments with high removal and low damage rates. This study provides a reference for the low-damage harvesting of fresh safflower. Key words: harvest; end-effector; fresh safflower; clamping; root-cutting DOI: 10.25165/j.ijabe.20251802.9461 Citation: Zhang Z G, Zeng C, Xu P, Shi R M, Wang Y Z, Xing Z Y. Clamping root-cutting end-effector for harvesting fresh safflower. Int J Agric & Biol Eng, 2025; 18(2): 146–154.